2021
DOI: 10.1108/jsfe-11-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the effect of fire retardant materials on timber

Abstract: PurposeThe fire safety of structures is an existing and important design aspect, which is assured by strict regulations. As a means to adhere to the strict requirements, fire protection has become a core problem. It is particularly difficult to comply with these regulations in the case of timber, which is a combustible material. These problems could be solved by enveloping the wood in fire retardant materials. MSZ EN 1995-1-2 currently does not take into consideration the fire-retardant materials charring rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The experimental matrix is shown in Table 2. Only one specimen was used for each case because previous experiments showed that in case of these tests the standard deviation was small (Lubloy et al, 2021). The specimens were cut from 150 3 150 3 45 mm blocks.…”
Section: Experiments Structure Of Mistreated Specimensmentioning
confidence: 99%
“…The experimental matrix is shown in Table 2. Only one specimen was used for each case because previous experiments showed that in case of these tests the standard deviation was small (Lubloy et al, 2021). The specimens were cut from 150 3 150 3 45 mm blocks.…”
Section: Experiments Structure Of Mistreated Specimensmentioning
confidence: 99%
“…However, due to its flammable nature, concerns regarding its safety in fire situations arise. While wooden components with a large cross-section may char and resist fire to some extent [4,5], pieces with smaller cross-sections require additional protection through coating with non-combustible materials [6] or treatment with fire-retardant compounds [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the fire resistance of wood increases its reliability and safety as a construction material [1,5,6]. Tannins, characterized by their renewable nature and low toxicity to human health, hold promise for this purpose [37].…”
Section: Introductionmentioning
confidence: 99%